2007
DOI: 10.1038/sj.ijo.0803549
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol metabolism and body composition in women: the effects of moderate weight loss

Abstract: Objective: To determine how moderate weight loss protocol through diet and exercise may affect changes in body composition, to determine the effects of weight loss on cholesterol metabolism and to examine the relationship between cholesterol metabolism and changes in body composition. Design: Thirty-five otherwise healthy, hypercholesterolemic women completed a 24-week weight loss study. A 20% decrease in energy intake through diet and a 10% increase in energy expenditure by exercise were combined with motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…A similar relationship has been reported previously in trials looking at caloric restriction, weight loss and their effect on cholesterol synthesis [ 39 - 41 ], however, few studies have examined the impact of caloric restriction on cholesterol absorption. Although two studies including diabetic subjects observed a negative relationship between cholesterol absorption and caloric intake [ 42 , 43 ], a more recent trial has shown no significant effect of caloric restriction or weight loss on cholesterol absorption [ 41 ]. Percent energy from saturated fat in the subjects' diet was negatively related to cholesterol synthesis across intervention groups.…”
Section: Discussionsupporting
confidence: 81%
“…A similar relationship has been reported previously in trials looking at caloric restriction, weight loss and their effect on cholesterol synthesis [ 39 - 41 ], however, few studies have examined the impact of caloric restriction on cholesterol absorption. Although two studies including diabetic subjects observed a negative relationship between cholesterol absorption and caloric intake [ 42 , 43 ], a more recent trial has shown no significant effect of caloric restriction or weight loss on cholesterol absorption [ 41 ]. Percent energy from saturated fat in the subjects' diet was negatively related to cholesterol synthesis across intervention groups.…”
Section: Discussionsupporting
confidence: 81%
“…Nutrient analyses also showed that caloric intake was negatively related to cholesterol absorption and positively to synthesis. A similar relationship has been reported previously in studies looking at caloric restriction, weight loss and their effect on cholesterol synthesis (Di Buono et al, 1999;Raeini-Sarjaz et al, 2001;Santosa et al, 2007); however few studies have examined the impact of caloric restriction on cholesterol absorption. Although two studies including diabetic subjects observed a negative relationship between cholesterol absorption and caloric intake (Simonen et al, 2000;Simonen et al, 2002), a more recent trial has shown no significant effect of caloric restriction or weight loss on cholesterol absorption (Santosa et al, 2007).…”
Section: Discussionsupporting
confidence: 56%
“…In contrast, it has recently been reported that a restricted weight-loss diet led to a reduction in cholesterol synthesis without changes in absorption capacity in women [35]. Moreover, variations in intakes of dietary fat or cholesterol were not accompanied by noticeable changes in cholesterol absorption markers in a short-term study in men [27].…”
Section: Discussionmentioning
confidence: 81%